Clinico-radiological Diagnosis of Optic Nerve Choristomas. (1st November 2020) - Juniat, Valerie; Patel, Sandy; Davis, Garry; Crompton, John L; Selva, Dinesh
ABSTRACT: Optic nerve choristomas are very rare lesions. They are characterised by the presence of fat cells, mesodermal collection of fibrous tissue and smooth muscle, and atrophic optic nerve tissue. Although the condition can be diagnosed on histology, it is not always possible to carry out surgical exploration for tissue diagnosis in view of the apical location of the lesion and the inherent risk to vision from surgery. Detailed neuro-imaging becomes vital in these cases for diagnosis. We report a case of a patient with an optic nerve choristoma diagnosed on neuroimaging, review the current literature related to this condition, and discuss the key clinico-radiological features of optic nerve choristomas.